2014
DOI: 10.5812/ircmj.16099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lidocaine Volume and Concentration on Preventing Incidence and Severity of Propofol Injection Pain

Abstract: Background:Propofol is one of common anesthetic drugs used in anesthesia. The most common side effects of propofol are local pain. Pretreatment with lidocaine can reduce propofol injection pain.Objectives:The aim of the present study was to assess and compare the efficiency of lidocaine 0.4% and 2% in reducing the incidence and severity of propofol injection pain.Patients and Methods:This was a double blind prospective clinical trial on children 4-8 years old with class ASA I and II candidates who were referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…This was in accordance with the study by Gharavi M et al, in which there was significant difference in pain perception using NRS pain score between the group B (0.4%) and group A (2%). 18 This study also showed a highly significant reduction in the withdrawal movements in the group A compared to the group B with a p value of 0.041. The incidence of pain in the group A was 8% (6 patients) and the highest score recorded was 1, according to the WRS score, while in the group B , the incidence of pain with propofol injection was 27% (14 patients) and the highest score recorded was one according to the WRS score.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This was in accordance with the study by Gharavi M et al, in which there was significant difference in pain perception using NRS pain score between the group B (0.4%) and group A (2%). 18 This study also showed a highly significant reduction in the withdrawal movements in the group A compared to the group B with a p value of 0.041. The incidence of pain in the group A was 8% (6 patients) and the highest score recorded was 1, according to the WRS score, while in the group B , the incidence of pain with propofol injection was 27% (14 patients) and the highest score recorded was one according to the WRS score.…”
Section: Discussionsupporting
confidence: 55%
“…Taking 80% power and a 5% level of significance, a sample size of total 126 patients, 63 in each group, was found to be sufficient to detect a clinically important difference of 20% between groups in using a two-tailed ztest of proportions. The 20% assumption was made on the basis of findings of a study done by Gharavi et al 18…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…21 Among these studies, the most commonly accepted technique is the administration of lignocaine just before the injection of propofol. 22 A study investigating the optimal dose of lidocaine for the prevention of injection pain due to propofol, found that the addition of 0.1mg/kg of lidocaine to 2.5 mg/kg of propofol decreased the pain, whereas increasing the dose of lidocaine to 0.2 or 0.4 mg/kg did not bring additional benefit. 23 Another study concluded that, the addition of 10 mg of lidocaine to propofol 2 mg/kg, or the administration of 1 mg/kg of lidocaine 30 seconds before the administration of propofol 2 mg/kg, effectively decreased pain caused by propofol injection.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Among these studies, the most commonly accepted technique is the administration of lignocaine just before the injection of propofol. [20]…”
Section: Discussionmentioning
confidence: 99%